Solid Fermentation of Pelletized Fish Feeds Containing Black Soldier Fly (Hermetia illucens) Larvae Meal to Enhance Growth Performance of Catfish (Clarias sp.) - Cita Mahardika Hariyono; Catur Sriherwanto; Harijono Harijono (Journal of Aquaculture and Fish Health, 2022)
Unsustainable use of fish meal as protein and lipid ingredients in aquafeed has driven the search for alternative. Black soldier fly (BSF) (Hermetia illucens) larvae have been widely studied for the substitution purpose. This study aims at investigating the effect of solid fermentation of pelleted diets containing BSF larvae meal (BSFLM) on the growth performance of catfish Clarias sp. Four feed pellets were formulated: F1 (non-fermented, 60% BSFLM), F2 (fermented, 60% BSFLM), F3 (non-fermented, 50% BSFLM), and F4 (fermented, 50% BSFLM). These formulated diets and commercial feed pellets (positive control) were separately fed to the catfishes in 5 aquaria (10 fishes per aquaria in triplicate). Results showed that the fermentation increased the protein level by 10–11%, but kept the crude lipid concentrations unchanged. Specific growth rate (SGR) and weight gain (WG) profiles for fermented feeds F2 and F4 were higher than the non-fermented feeds F1 and F3, respectively. F4  gave the best feed conversion ratio (FCR) of 1.78, which was 15–25% more efficient than F1, F2, and F3. Compared to the commercial feed, the 4 formulated feeds underperformed by around 50% in all of the growth parameters except survival rates (SR) which were not significantly different  (93–100%).